DISABANK iMOBILE / Muhammad Zameer Sutiman … [et al.] - Sutiman, Muhammad Zameer; -, Puteri Nursalsabella Nizriena; -, Nurlianaelyshah; -, Nur Afiqah Balqis; Johari, Muhammad Husaini; Mazzuri, Nurfarisha; Harun, Hazalinda (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Online banking has been developed as an alternative for people who preferred to go cashless than handling so much cash in hand. This is why scanning QR code has been common as a method of payment in majority of shops, however it is not disability friendly such as blind people because it uses password for login. Our objective is to create an inclusive and accessible banking environment where individuals of all abilities can confidently and comfortably engage in financial services. Through innovative design, empathetic customer service, and tailored solutions, we aim to break down barriers and empower people with disabilities to manage their finances independently, ensuring equal access to banking services for all. This innovation of banking apps is equipped with fingerprints and face id scanner to replace using normal password to login their account and doing any transactions. No more taking time for disabled people to log in into their bank account to do a payment. It also has a text to speech feature for every text that been shown in the apps. This led to easing the process of banking for disabled people and improve their financial experience to be more hassle free.